2021
DOI: 10.1021/acs.jmedchem.0c02009
|View full text |Cite
|
Sign up to set email alerts
|

Imidazopyridine-Based 5-HT6 Receptor Neutral Antagonists: Impact of N1-Benzyl and N1-Phenylsulfonyl Fragments on Different Receptor Conformational States

Abstract: G-protein coupled receptors (GPCRs) exist in an equilibrium of multiple conformational states, including different active states, which depend on the nature of the bound ligand. In consequence, different conformational states can initiate specific signal transduction pathways. The study identified compound 7e, which acts as a potent 5-hydroxytryptamine type 6 receptor (5-HT 6 R) neutral antagonist at Gs and does not impact neurite growth (process controlled by Cdk5). MD simulations highlighted receptor conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 59 publications
(121 reference statements)
3
31
0
Order By: Relevance
“…Selectivity Profiles of Selected Compounds. The most potent compounds (K i ≤ 30 nM) exhibiting structural (18,22,28) and enantiomeric (27,28) diversity were further evaluated for their selectivity over serotonin receptors (5-HT 1A R, 5-HT 2A R, 5-HT 7 R) and dopamine D 2 receptor (D 2 R) in radioligand binding assays. The tested compounds displayed high selectivity over 5-HT 1A , 5-HT 2A , 5-HT 7 , and D 2 receptors (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selectivity Profiles of Selected Compounds. The most potent compounds (K i ≤ 30 nM) exhibiting structural (18,22,28) and enantiomeric (27,28) diversity were further evaluated for their selectivity over serotonin receptors (5-HT 1A R, 5-HT 2A R, 5-HT 7 R) and dopamine D 2 receptor (D 2 R) in radioligand binding assays. The tested compounds displayed high selectivity over 5-HT 1A , 5-HT 2A , 5-HT 7 , and D 2 receptors (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic procedures for intermediates 5 and 6 and final compounds (7−32) as well as characterization data for selected final compounds (18,22,27,28) are presented below. The synthesis of intermediates 1−4 was performed according to the previously described procedures 19,20 and is reported in the Supporting Information together with spectroscopic data for all intermediates and remaining final compounds.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT 6 R antagonists improve cognitive performance in a wide range of preclinical models of cognitive impairment. 19 21 The beneficial effects of 5-HT 6 R antagonists on cognition have been attributed to the enhanced release of acetylcholine and glutamate in the frontal cortex and hippocampus. 22 , 23 Finally, the selective 5-HT 6 R antagonists—idalopirdine and AVN-211—have advanced to phase II and phase IIa clinical trials, respectively, as add-on therapies against schizophrenia, but the results were not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the 5-HT 6 R interactome identified additional signaling pathways, including the Fyn tyrosine kinase, mechanistic target of rapamycin (mTOR, involved in synaptic plasticity and cognition), and cyclin-dependent kinase 5 (Cdk5) pathway, which is critical for neuron migration and neurite growth. 5-HT 6 R antagonists improve cognitive performance in a wide range of preclinical models of cognitive impairment. The beneficial effects of 5-HT 6 R antagonists on cognition have been attributed to the enhanced release of acetylcholine and glutamate in the frontal cortex and hippocampus. , Finally, the selective 5-HT 6 R antagonistsidalopirdine and AVN-211have advanced to phase II and phase IIa clinical trials, respectively, as add-on therapies against schizophrenia, but the results were not conclusive. , …”
Section: Introductionmentioning
confidence: 99%